Local climate change and society - Salih, Mohamed Abdel Rahim M. (Routledge advances in climate change research, 2013)
"This book aims at creating contact points between the current academic and policy debate's obsession with global-centered to the most neglected local-centered concerns with climate change. Although climate change impacts on the environmental life support system are global, its manifestations and subsequent consequences are social and therefore local. Therefore this book gives special attention to the significance of local communities and local governments' formal and informal adaptation and mitigation responses. Local Climate Change and Society articulates how climate change alters society-environment relationships, contributing to structural changes in local communities and societies relationship to environmental resources and economic opportunities essential for eking a living and leading a healthy life. The book consists of 12 Chapters and case studies from across the globe, written by academics, researchers and policy makers at the cutting edge of climate change studies. The main sub- themes covered by this book include: of the book are as follows: conceptualizing local climate change and society relations; analyzing and explaining local government response to local climate change, particularly adaptation/mitigation; Micro-climate policies and responses; and climate social movements and activism in South-North perspectives"--